Patton : battling with history - Daniel, J. Furman, III (American military experience series., 2020)
"General George S. Patton Jr. is one of the most successful and misunderstood generals in history. Despite the hundreds of books and articles written on the famous general, none fully capture how his successes were based on his study of the past. This thematic biography traces Patton's life-long obsession with history and argues that his success was based on his unique ability to consume, produce, and apply history."--